Kesiapan Mahasiswa Universitas Dharma Andalas dalam Pembelajaran Daring di Masa New Normal - Mellyna Eka Yan Fitri; Lasty Yossi Hastini; Lucy Chairoel (Universitas Dharma Andalas, 2023)
Higher education institutions, as advanced learning providers, require all students to keep up with technological developments and apply them in online learning. There are many challenges faced by both lecturers and students, ranging from supporting electronic devices, signal strength, data quotas, to students' skills in utilizing technology for learning. Initially, they were not prepared, but now they must be ready for online learning. A random sample of 200 respondents from the undergraduate Management program at Dharma Andalas University provided results showing that the Attitude Towards The Behaviour variable has the strongest influence on the Intention variable, followed by Subjective Norms, and then Perceived Behavioral Controls. So far, students' readiness for online learning is quite good, and they even hope that the campus continues online learning, but with the inclusion of face-to-face learning. ABSTRAK Perguruan tinggi sebagai pembelajaran lanjutan mewajibkan seluruh mahasiswa untuk mengikuti perkembangan teknologi dan menerapkannya dalam pembelajaran daring ini. Banyak kendala yang dihadapi oleh dosen dan mahasiswa mulai dari perangkat elektronik yang mendukung, sinyal, kuota dan keterampilan mahasiswa dalam menggunakan teknologi untuk pembelajaran. Pada awalnya mereka tidak siap namun hingga sekarang mereka harus siap untuk pembelajaran daring. Sampel yang dipilih secara acak sejumlah 200 responden mahasiswa program studi S1 Manajemen Universitas Dharma Andalas yang memberikan hasil bahwa variabel Attitude Towards The Behaviour mempengaruhi variabel Intention paling kuat, selanjutnya Subjective Norms dan selanjutnya Perceived Behavioural Controls. Sejauh ini kesiapan mahasiswa untuk melakukan pembelajaran daring adalah cukup baik dan bahkan mereka berharap kampus tetap melakukan pembelajaran daring, namun tetap ada pembelajaran tatap muka.